Effect of daidzein on CYP1A2 activity and pharmacokinetics of theophylline in healthy volunteers - Peng, Wen-Xing; Li, Huan-De; Zhou, Hong-Hao (European journal of clinical pharmacology, 2003)
To examine the potential effect of daidzein on CYP1A2 activity and on the pharmacokinetics of theophylline by inhibiting its metabolism. The experiment was conducted in a single-blind, placebo-controlled, parallel study. The caffeine metabolic ratio (CMR) used as an indicator of CYP1A2 function was completed at baseline and after daidzein or placebo co-administration. A single dose of 100 mg theophylline was taken by all 20 volunteers on day 3. Thereafter, volunteers were allocated for one of two regimens. One group received 200 mg daidzein twice daily for 10 days. The other group received placebo. On day 12, the test group received 200 mg daidzein with 100 mg theophylline; the parallel group received 100 mg theophylline with placebo. The baseline value of CMR between test group and control group did not show a difference (P=0.215). The percentage decrease in CMR ranged from -50% to 20%, with an average value of -19.8+/-19.7%. The percentage decrease in test group was statistically significant (P=0.009), and no significant changes were shown in the control group (t=0.12, P=0.914). By comparing the pharmacokinetic parameters of theophylline before and after daily treatment with daidzein, the effect of daidzein on the metabolism of theophylline was evident. Comparing the kinetics parameters of theophylline of day 1 (without co-medication) with those of day 12 (10-day daidzein), the AUC(0-48), AUC(0- infinity ), C(max) and t(1/2) were significantly increased by 33.57+/-21.75% (CI, 1.21-1.46, P< 0.05), 33.77+/-21.45% (CI, 1.20-1.46, P<0.05), 23.54+/-16.93% (CI, 1.23-1.52, P< 0.05) and 41.39+/-45.92% (t=-3.19, P=0.011), respectively. The pharmacokinetic parameters of theophylline within the placebo group showed no statistically significant difference (P >0.05). Daidzein, a principal isoflavone in soybean, in higher doses may inhibit CYP1A2 activity in vivo, and physicians should be aware of potential drug-food interactions.